Self-esteem, narcissism, and dimensions of juvenile delinquency: Clarifying the relation - Braga, Teresa (2018)
The present study aimed to analyze the predictive capacity of self-esteem and narcissism of two dimensions of juvenile delinquency: crime seriousness and age of criminal onset. With a total sample of 261 youths from the juvenile justice system, an ordinal regression model was estimated with crime seriousness as the dependent variable, and a linear regression model was estimated with age of crime onset as the dependent variable. The results showed that narcissism predicts crimes seriousness and has a marginally significant effect on age of crime onset, revealing its importance as a risk factor for both dimensions of delinquency and supporting its inclusion in intervention programs for delinquency. On the other hand, the results revealed that self-esteem did not predict neither crime seriousness nor age of criminal onset. Future studies should continue to explore the role of self-esteem in predicting delinquency in order to better clarify this relationship.